2013
DOI: 10.1177/0893318913498824
|View full text |Cite
|
Sign up to set email alerts
|

Which Identities Matter? A Mixed-Method Study of Group, Organizational, and Professional Identities and Their Relationship to Burnout

Abstract: Considerable research views group, organizational, and professional identities as theoretically and methodologically similar. This study suggests that these identities are generically different. An explanatory sequential mixed data analysis of survey and interview data collected at an information technology organization (N = 111 workers) was used to examine the relationships between identities and the experience of burnout and to understand the communicative behaviors associated with types of identity and burn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 63 publications
3
46
0
Order By: Relevance
“…This result is confirmed by the findings of Av anzi et al (2015) who find negative correlatio n between the identification levels and burnout of teachers. Also, Lammers et al (2013) show that there is significant negative correl ations between OI and emotional exhaustion and depersonalization dimensions of burnout. According to the results, OI play s a parti al intermediary role in the influence of PSS on OCB.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This result is confirmed by the findings of Av anzi et al (2015) who find negative correlatio n between the identification levels and burnout of teachers. Also, Lammers et al (2013) show that there is significant negative correl ations between OI and emotional exhaustion and depersonalization dimensions of burnout. According to the results, OI play s a parti al intermediary role in the influence of PSS on OCB.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, the correlation between teacher's organizational identities and burnout plays a intermedi ary rol e in their perceptions of social support. Lammers, Atouba & Carlson (2013) found significant negative correlations between organizational identification and emotional exhaustion and depersonalization dimensions of burnout. Supervisor support is positively correlated positively to organizational citizenshi p behavior (Yadav & Rangnekar, 2014;Chen, Wang, Chang & Hu, 2008;Ozdemir, 2010;Wang, 2014) and negatively to burnout (Avanzi et al,2015;Brackett et al, 2010;Guarana, 2010;Kahn et al, 2006).…”
Section: Organizational Citizenship Behavior (Ocb)mentioning
confidence: 84%
“…Employees reported a willingness to exhibit a great deal of discretionary effort, but did not indicate any associated negative impacts. This is consistent with research that suggests identification with one's work group can limit the damaging effects of intensification or burnout (Lammers, Atouba, & Carlson, ). Encouraging growth and expression of opinions was also common, with participants appearing to view it as offering a source of competitive advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Avanzi et al (2015) report that organizational identification negatively affects emotional exhaustion and reduced personal accomplishment. In addition, Kemp et al (2013) have found a negative and significant relationship between organizational identification and emotional exhaustion, and Wegge et al (2006) and Lammers et al (2013) verify that organizational identification negatively and significantly affects emotional exhaustion and depersonalization. In addition, Wegge et al (2006) clarify the positive relationship between organizational identification and personal accomplishment.…”
Section: Theoretical Implicationsmentioning
confidence: 91%
“…The studies focusing on the relationship between organizational identification and burnout show that organizational identification negatively affects burnout (Rode et al, 2012), emotional exhaustion (Avanzi et al, 2015; Kemp et al, 2013; Lammers et al, 2013) and depersonalization (Wegge et al, 2006;Lammers et al, 2013). On the other hand, there are differences in the findings of the relationship between organizational identification and personal accomplishment because some studies deal with personal accomplishment as reduced personal accomplishment.…”
Section: 3 Organizational Identification and Burnoutmentioning
confidence: 99%